2021
DOI: 10.1186/s12887-021-02705-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for metabolic bone disease among preterm infants less than 32 weeks gestation with Bronchopulmonary dysplasia

Abstract: Background Bronchopulmonary dysplasia (BPD) infants present an increased incidence of metabolic bone disease (MBD), but it is unknown which factors contribute to this. The aim of this study was to determine the risk factors for developing MBD in BPD infants. Methods A retrospective review of the medical records of BPD infants admitted to the Neonatal intensive care unit at Zhangzhou Hospital between Jun 2016 and May 2020 was performed. BPD infants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…A significant difference was also found in the incidence of bronchodysplasia and in the longer duration of mechanical and noninvasive ventilation in infants at increased risk. These data confirm the findings of the previous published studies [2,10,27,28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A significant difference was also found in the incidence of bronchodysplasia and in the longer duration of mechanical and noninvasive ventilation in infants at increased risk. These data confirm the findings of the previous published studies [2,10,27,28].…”
Section: Discussionsupporting
confidence: 93%
“…The increased length of the stay in our population at risk confirms what was reported in previous study by Chen and coworkers [25,27].…”
Section: Discussionsupporting
confidence: 92%
“…Greer et al compared 16 VLBW infants with BPD against 16 VLBW infants without BPD who were matched for GA and found no differences in energy, calcium, vitamin D, or phosphorous intake in the first 60 days of hospitalization nor any significant difference in weight, length, head circumference, or bone mineral content at 12 months of age between the two groups 14 . Among infants with BPD, Chen et al found risk factors for metabolic bone disease included prolonged (>2 weeks) use of diuretics, cholestasis, fetal growth restriction, length of stay, extremely low birth weight, and feeding volume <80 ml/kg/day at the end of the fourth week after birth 15 …”
Section: Resultsmentioning
confidence: 99%
“…According to the findings, this nutritional inadequacy seems to be related to the lower volume of diet offered, which also reflects a lower mineral supply and contributes to the occurrence of osteopenia. As shown by Chen et al [ 16 ], reduced enteral diet volume is a risk factor for osteopenia. The volume of human milk provided early in postnatal life is positively associated with bone mineral content [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The low solubility and precipitation of nutrients is a problem reported in studies that address osteopenia of prematurity, especially in the face of prolonged use of parenteral nutrition as the sole or main dietary source [ 12 ]. Therefore, along with parenteral nutrition, early enteral nutrition is recommended [ 16 ].…”
Section: Discussionmentioning
confidence: 99%